Advancing the Monetary Policy Toolkit through Outright Transfers - Buetzer, Sascha (IMF Working Papers; Working Paper, 2022)
This paper argues that in reserve currency issuing economies at the effective lower bound, outright transfers from the central bank to households are both more equitable and more effective in achieving monetary policy objectives than asset purchases or negative interest rates. It shows that concerns pertaining to central banksa' policy solvency and equity position can be addressed through a careful assessment of a central bank's loss absorbing capacity and, if need be, tiered reserve remuneration policies. It also spells out key differences to a debt or money financed fiscal stimulus, which are particularly pronounced in a currency union without a central fiscal capacity. The paper concludes by discussing broader institutional, political, and legal considerations.